Student well-being, academic performance, and life satisfaction during the COVID-19 pandemic - Mbuma, Nokulunga Winnie (College of Accounting, 2024)
Well-being includes emotional, psychological, and social well-being. Our wellbeing is inspired by our thoughts, feelings, actions, and how we react to stress, interact with others, and decision making. Well-being has the potential to negatively affect academic achievement and be a significant public health challenge. This study investigated the relationship between student mental health and life satisfaction, and academic performance during the Covid-19 pandemic. The study also assessed the extent of first-year university students flourishing and languishing. Cross-sectional survey data were collected from the first-year University of Cape Town Commerce students. A total of 395 first-year commerce students completed the questionnaire; however, after cleaning the data and applying the sample frame criteria, only 242 questionnaires were used N = 242; 132 females and 110 males for this study. Student wellbeing, resilience, and life satisfaction was measured using the Mental Health ContinuumShort Form (MHC-SF), Brief Resilience Scale (BRS), and Satisfaction with Life Scale (SWLS), respectively. Demographic variables were also included in the survey. Multiple regression analyses were performed to assess the relationship between the three well-being dimensions, academic performance, and life satisfaction. Only emotional well-being (EWB) significantly explained the difference in academic performance. The results also show that increasing student well-being leads to positive outcomes such as higher perceived life satisfaction and improved academic performance. Resilience did not moderate the relationship between the three well-being dimensions of positive mental health and academic performance. Based on the results of this study, it appears that there is a need to explore ways to improve student well-being by providing universities and students with opportunities to access well-being interventions. Keywords: Mental health, well-being, university students, academic performance, life satisfaction.